Proposed energy management for a decentralized DC-microgrid based PV-WT-HESS for an isolated community - Hafsi Oussama; Abdelkhalek Othmane; Hartani Mohammed Amine; Chakar Abdesselam; Soumeur Mohammed Amine (Institute of Advanced Engineering and Science, 2020)
Microgrids are small-scale power systems destined to supply isolated villages and optimum utilization of renewable energies. For this reason, this paper presents a DC-MG of 150 Kwp to feed an island village. The configuration of the proposed system consists of four interconnected sub-sections supplied by the centralized unit through PV and Wind Distributed Energy Resources DERs, in addition to the supercapacitor storage device. In the other hand, internal batteries of each sub-section cover its load demand separately, where electrical and chemical storage devices can be advantageous hybrid energy storage system HESS for the system. Thus, the control structure of the DC-MG is based on current hysteresis method to assure the charge/discharge operation and the stability of the DC-bus voltage, then a proposed management strategy to manage the shared energy of the DCMG system. The system behavior is tested under variable parameters and conditions using Matlab/Simulink.